Hyperlactatemia in patients undergoing adult cardiac surgery under cardiopulmonary bypass: Causative factors and its effect on surgical outcome - Rakesh Naik; Gladdy George; Sathappan Karuppiah; Madhu Andrew Philip (Annals of Cardiac Anaesthesia, 2016)
Objectives of the Study: To identify the factors causing high lactate levels in patients undergoing cardiac surgery under cardiopulmonary bypass (CPB) and to assess the association between high blood lactate levels and postoperative morbidity and mortality. Methods: A retrospective observational study including 370 patients who underwent cardiac surgeries under cardiopulmonary bypass. The patients were divided into 2 groups based on serum lactate levels; those with serum lactate levels greater than or equal to 4 mmol/L considered as hyperlactatemia and those with serum lactate levels less than 4 mmol/L. Blood lactate samples were collected intraoperatively and postoperatively in the ICU. Preoperative and intraoperative risk factors for hyperlactatemia were identified using the highest intraoperative value of lactate. The postoperative morbidity and mortality associated with hyperlactatemia was studied using the overall (intraoperative and postoperative values) peak lactate levels. Preoperative clinical data, perioperative events and postoperative morbidity and mortality were recorded. Results: Intraoperative peak blood lactate levels of 4.0 mmol/L or more were present in 158 patients (42.7%). Females had higher peak intra operative lactate levels (P = 0.011). There was significant correlation between CPB time (Pearson correlation coefficient r = 0.024; P = 0.003) and aortic cross clamp time (r = 0.02, P = 0.007) with peak intraoperative blood lactate levels. Patients with hyperlactatemia had significantly higher rate of postoperative morbidity like atrial fibrillation (19.9% vs. 5.3%; P = 0.004), prolonged requirement of inotropes (34% vs. 11.8%; P = 0.001), longer stay in the ICU (P = 0.013) and hospital (P = 0.001). Conclusions: Hyperlactatemia had significant association with post-operative morbidity. Detection of hyperlactatemia in the perioperative period should be considered as an indicator of inadequate tissue oxygen delivery and must be aggressively corrected.